Increased frequency of CD4+PD‐1+HLA‐DR+ T cells is associated with disease progression in CLL. (8th November 2019) - Elston, Lauren; Fegan, Chris; Hills, Robert; Hashimdeen, Shaikh S.; Walsby, Elisabeth; Henley, Peter; Pepper, Chris; Man, Stephen
Summary: Chronic lymphocytic leukaemia (CLL) patients often have abnormal expansions of CD4 + and CD8 + T cells and this can be associated with progressive disease. To characterise the key T‐cell populations involved in this phenomenon, we used flow cytometry and 11 phenotypic markers to study 74 CLL patients and 14 controls. T cells of CLL patients were more phenotypically complex than those of healthy controls with significant increases in the frequencies of CD4 and CD8 memory T cells expressing exhaustion‐, activation‐ and senescence‐associated markers. Multivariate analysis of 111 different T‐cell subsets showed that high frequencies of four subsets (three CD8 and one CD4) were associated with shorter progression‐free survival. The most significant association was with CD4 + HLA‐DR + PD‐1 + T cells, and patients could be stratified into high‐ and low‐risk groups based on the frequency of these T cells. The expansion of this CD4 + subset could not be accounted for by age, cytomegalovirus infection or increases in Treg cells. Overall, these results highlight two relatively simple biomarkers, percentage CD8 + and percentage CD4 + PD‐1 + HLA‐DR + T cells, which can be used to risk‐stratify CLL patients, independent of other tumour‐associated markers. They also provide further evidence for the pivotal role of T cells in modulating the pathology of CLL.